THE COURSE IN C.P.A. PROBLEMS. - Taylor, Jacob B. (The Accounting Review, 1935)
A course in CPA problems is universally accorded a place in the curriculum in the senior year and represents the end of the work in accounting for the accounting major. Here is an attempt to bring in materials from the outside with which to test the mettle of the prospective accounting practitioner. Here is a departure from the consistent use of materials created by university teachers in accounting to extend and develop the teaching of accounting principles. Perhaps to the alert student, there is carried a warning of harder days to come, of more complex problems to solve in the work which lies ahead. In searching for the specific purpose of a course in CPA problems, it can be stated that it should provide a thoroughgoing review of accounting principles and practices. This means that by the use of CPA problems an attempt should be made to cover the field of accounting in review.